Clitoral Phimosis: Effects on Female Sexual Function and Surgical Treatment Outcomes - Chmel, Roman; Nováčková, Marta; Fait, Tomáš; Zámečník, Libor; Krejčová, Lucie; Pastor, Zlatko (The journal of sexual medicine, 2019)
BACKGROUND: Surgery is the optimal treatment for a severe form of clitoral phimosis (CP) that is initiated by lichen sclerosus (LS) and causes female sexual dysfunction. AIM: We aimed to determine the etiology of clitoral phimosis, its influence on sexual function, and outcomes after surgical treatment. METHODS: In this prospective cohort study, we observed the occurrence of clitoral phimosis and related changes in a group of 3,650 sexually active heterosexual women with a mean age of 34.8 ± 14.9 years (20-45 years) from September 2014 to September 2016. Ultimately, we compared the changes in sexual function and distress and satisfaction with postoperative genital appearance in 9 patients with severe clitoral phimosis at 12 months after surgical treatment. MAIN OUTCOME MEASURES: Sexual function was evaluated using the Female Sexual Distress Scale-Revised and the Female Sexual Function Index, and the patient's genital self-image was evaluated using the Female Genital Self-Image Scale; gynecologic examinations were performed on all patients. RESULTS: Various forms of CP were found in 46 of 3,650 patients (1.3%). Severe forms of CP were found in 9 cases, but it was complicated by stenosis of vaginal introitus in only 2 cases. These 9 patients underwent circumcision, and 2 of them underwent perineoplasty. Female sexual dysfunction occurred mainly in those with LS and severe forms of phimosis. Sexual function, as indicated by the total Female Sexual Function Index score, was significantly improved at 12 months after surgery (17.9 ± 0.9 vs 26.6 ± 0.5; P < .001). The Female Genital Self-Image Scale score assessing genital perception was significantly higher after surgery than before in women who underwent clitoral circumcision (20 ± 3.0 vs 12.3 ± 3.3; P < .001). The Female Sexual Distress Scale-Revised score was significantly lower after surgery than before (21.3 ± 6.2 vs 33.8 ± 6.9; P < .001). Sexual function in 2 women with CP and stenosis of vaginal introitus improved after surgery, but the sexual distress level did not decrease significantly. CLINICAL IMPLICATIONS: The results of this study will help clinicians to centralize treatment methods and advise patients on the management of clitoral phimosis. STRENGTHS & LIMITATIONS: This is a study evaluating postoperative results of sexual function, distress, and satisfaction with genitalia in women with severe CP, using validated questionnaires. However, the small number of patients and the absence of an appropriate control group are limitations. CONCLUSION: Surgical treatment of clitoral phimosis can improve sexual function, but because LS-a common underlying cause-is chronic in nature, patients may experience recurrence. Chmel R, M Nováčková, Fait T, et al. Clitoral Phimosis: Effects on Female Sexual Function and Surgical Treatment Outcomes. J Sex Med 2019;16:257-266.
Keywords: zdravotnické služby pro ženy; Humans; sexualita; lichen sclerosus vulvy; lidé středního věku; Women's Health Services; kohortové studie; Female; mladý dospělý; dospělí; výsledek terapie; lidé; Plastic Surgery Procedures; Cohort Studies; Adult; Sexuality; ženské pohlaví; zákroky plastické chirurgie; představa o vlastním těle; Middle Aged; Treatment Outcome; Vulvar Lichen Sclerosus; Young Adult; Body Image; Clitoris; prospektivní studie; klitoris; Prospective Studies